2022
DOI: 10.1126/sciadv.abl5716
|View full text |Cite
|
Sign up to set email alerts
|

NGF-p75 signaling coordinates skeletal cell migration during bone repair

Abstract: Bone regeneration following injury is initiated by inflammatory signals and occurs in association with infiltration by sensory nerve fibers. Together, these events are believed to coordinate angiogenesis and tissue reprogramming, but the mechanism of coupling immune signals to reinnervation and osteogenesis is unknown. Here, we found that nerve growth factor (NGF) is expressed following cranial bone injury and signals via p75 in resident mesenchymal osteogenic precursors to affect their migration into the dama… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 44 publications
(51 reference statements)
3
35
0
Order By: Relevance
“…After injury, inflammatory signals cause bone regeneration to commence simultaneously with infiltration by sensory nerve fibers. Xu et al [ 42 ] demonstrated that cranial bone injuries stimulate nerve growth factor expression and signaling via p75 in resident osteogenic precursors that affect their migration into the damaged tissue, thus suggesting that nerve growth factor-p75 signaling has potential roles in bone regeneration. Ambrosi et al [ 43 ] reported that intrinsic skeletal stem cell aging in mice alters signaling in the bone marrow niche to a degenerative inflammatory niche, thus leading to poorly regenerated bones because of fragility.…”
Section: Stem Cell Signals In the Regulation Of Tissue Regenerationmentioning
confidence: 99%
“…After injury, inflammatory signals cause bone regeneration to commence simultaneously with infiltration by sensory nerve fibers. Xu et al [ 42 ] demonstrated that cranial bone injuries stimulate nerve growth factor expression and signaling via p75 in resident osteogenic precursors that affect their migration into the damaged tissue, thus suggesting that nerve growth factor-p75 signaling has potential roles in bone regeneration. Ambrosi et al [ 43 ] reported that intrinsic skeletal stem cell aging in mice alters signaling in the bone marrow niche to a degenerative inflammatory niche, thus leading to poorly regenerated bones because of fragility.…”
Section: Stem Cell Signals In the Regulation Of Tissue Regenerationmentioning
confidence: 99%
“…Loss of Rictor in osteoblasts impairs bone mass and strength [41,42]. The role of nerve growth factor (NGF) in spinal cord injury repair and bone fracture repair has been extensively studied [43,44]. Previous studies have supported the predicted main regulatory factors Rictor and TEAD1, and suggested that the roles of torin1, DDX5, and CAB39L in the spinal cord and bone warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Both receptors were first expressed on neurons to accompany the function of NGF in regulating neuron survival and growth. Later, they were found expressed on bone linage cells and involved in the bone repair process ( 57 59 ). Tomlinson et al ( 60 ) found that the NGF-TrkA axis is of great importance to bone formation under mechanical loading in mice.…”
Section: Signaling Molecules From Nerves To Bone and Their Applicatio...mentioning
confidence: 99%